Přínos evropských imigrantů pro rozvoj venezuelské ekonomiky a vliv současné vlády H. Cháveze - Stiegler, Pavel (Univerzita Pardubice, 2010)
This paper is focused on the description of the influence of European Immigrants on Venezuelan industry, retail sector, wholesale and franchise. The key factor in the development of Venezuelan modern industry played european immigrants. It is also intended to analyse the impact of the changes implemented by the Government of the president Hugo Chávez and of the Socialism of the 21. Century on the Venezuelan economy - what could be improved, mainly in the public-private relationship. Regarding the globalization the paper also focuses on the regional initiatives of Venezuelan prezident H. Chávez and the impact on the Region of Central America and the Caribbean.
Keywords: Latin America and the Caribbean; socialism of the 21. century; Hugo Chávez; european immigrants; retail and franchise sector in Venezuela